Lubâb At-Ta’wîl ‘Inda Al-Imâm Al-Khâzîn Baina Al-Ma’tsûr wa Ar-Ra’yi (Dirâsah Maudhu’iyyah fi Ayah al-Qashash) - Muhammad Shulhi Alhadi Siregar (Universitas Darussalam Gontor, 2018)
Abstrak This paper concern to study about one of Tafseer book, namely Lubâb al-Ta'wîl fi Ma'âny at-Tanzîl by Imam al-Khazin. Some scholars differ in the setting of sources of tafseer. Such as, the well-known scholars, Muhammad Ali Iyazi and Muhammad Husain ad-Dzahabi. Ulama Iyazi assumes that Tafseer Khazin belongs to the category of commentary bi al-Ma'tsûr, since this commentary is an ikhtishar of Tafseer al-Baghawi. While some scholars such as adz-Dzahabi, categorized this tafseer into the bi al-Ra'yi. By using the tahlily documentation method and the thematic method associated with Qashash verses in the Qur'an, the researchers found the correct method, namely the tafseer of al-Atsary an-Nazhary or known by tafseer bi al-Ma'tsûr who use Ra'yi as an extension of explanation and the determination of the most powerful law, seen from writing theme related at the end of its tafseer.